France & Benelux [videorecording (DVD)] - Steves, Rick, 1955- (Back Door Productions, 2000)
Contains seven complete TV shows, first broadcast from 2000 to 2005, featuring: Paris, Normandy, Provence, French Riviera, Belgium, Amsterdam, Dutch side-trips, and more.